Factors of rowing ergometer performance in high-level female rowers - Bourdin, M.; Lacour, J.-R.; Imbert, C.; Messonnier, L. A. (International Journal of Sports Medicine, 2015)
The present study investigated morphological and physiological factors of rowing ergometer performance over 2000?m (P2000, W) in 70 national and international level [27 lightweight (LW) and 43 heavyweight (HW)] female rowers. Maximal oxygen uptake (VOmax, L.min-1), maximal aerobic power (Pamax, W), power output corresponding to 4 mmol.L-1 blood lactate concentration expressed in absolute (PLa4, W) and relative to Pamax (PLa4%, %) values, peak power output (Ppeak, W), and rowing gross efficiency (RGE, %) were determined during an incremental rowing test. In the whole group, Ppeak was the best predictor of P2000 (r=0.89, p<0.001), as it was shown in men. PLa4 (r=0.87), VO2max (r=0.83), body mass (r=0.65), and height (r=0.64) were also significantly correlated with P2000 (p<0.001 for all). Ppeak was also the best predictor of P2000 when the two sub-groups LW and HW were considered separately. It was concluded that Ppeak is an overall index of physiological rowing capacity in groups of high-level LW and HW female rowers. The predictive value of Ppeak is similar to that of PLa4, but Ppeak presents the advantage of being obtained with a simple ergometer test without biological measurements.